Perancangan Program Aplikasi Sistem Informasi Akuntansi Laporan Keuangan Menggunakan Microsoft Access 2016 (Studi Kasus Pada CV Mitra Tani Farm - Bogor) - Devi Elfiani; Darya Setia Nugraha (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
CV Mitra Tani Farm is a livestock company located in Bogor. The main activity of CV Mitra Tani Farm is buying and selling livestock to customers for aqiqah and qurban. However, the accounting records at CV Mitra Tani Farm are still manual and semi-manual so that there are several problems in the financial reporting process, such as a lack of employee knowledge about accounting so that financial recording and reporting are still unstructured and there a delay in submitting financial reports to the company owners. With these problems, the authors provide solutions by designing an application of financial report accounting information systems. The author uses qualitative methods with a case study approach and development. The author also conducts data observations and interviews to collect the required data. The results of this research is the design of a financial report application using Microsoft Access 2016 with flowchart and DFD in designing the system. The output from this application is containing general journal reports, ledgers, trial balance, income statement, capital change, balance sheet, cash flows, and sales report. This design is expected to solve the problems contained in financial reports accounting information system at CV Mitra Tani Farm.